A novel dynamic hydrant flushing framework facilitated by categorizing contamination events. Issue 3 (15th March 2020) - Khaksar Fasaee, Mohammad Ali; Nikoo, Mohammad Reza; Hashempour Bakhtiari, Parnian; Monghasemi, Shahryar; Sadegh, Mojtaba
ABSTRACT: Security of water distribution systems is of highest importance to public health. In this study, a novel dynamic hydrant flushing strategy is developed to remove the injected contamination mass in the shortest possible time after being detected by the sensors. The coupled EPANET-IHS simulation-optimization model is developed to determine the hydrant flushing strategies (the hydrant sets and their opening/closing time). This allows water utility managers to utilize the hydrants instantly after the sensor alarm with no need for excessive investigations, which enhances the flushing effectiveness. Developed based on thousands of contaminant injection scenarios (contamination events), the proposed hydrant flushing strategies are reliable to remove any injected contamination mass. Moreover, the operation of hydrant sets is dynamically validated by closing/opening of hydrants throughout the total hydrant flushing duration, which enables the model to flush up to more 20%. The methodology is examined on the mid-sized WDS of Mesopolis city.